PENINGKATAN PENGETAHUAN ANGGOTA KLUB JANTUNG SEHAT TENTANG SWAMEDIKASI PADA MASA PANDEMI COVID-19 DI DESA SIRNAGALIH PROPINSI JAWA BARAT - Trini Handayani; Taufiq Dwi Jatmika (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Self-medication is an act of self-medicating a minor illness at home without being examined by a doctor. If done according to the rules, self-medication can be used to cure diseases, but if it is not according to the rules, it can be dangerous and waste time and money. Based on the results of the 2013 Riset Kesehatan Dasar, there are still households that provide hard drugs that should be obtained by prescription from a doctor, used for self-medication. The purpose of this activity is to increase the knowledge of Klub Jantung Sehat members regarding safe self-medication, namely the right medicine, the right dose, the right indication and the right target. The socialization activities were carried out after the gymnastics in the hall of Sirnagalih Village. The methods used are lectures, demonstrations and questions and answers. In addition, a tutorial is delivered on how to check drugs that have been registered with the Badan Pengawas Obat dan Makanan through the BPOM Product Check account. As a result of this outreach, all members of the Sirnagalih Village of Klub Jantung Sehat understand about safe drugs that can be used for self-medication at home. About 50% of the medicines used for self-medication turned out to be ethical drugs that should have been obtained by prescription from a doctor. On that occasion it was also conveyed that the drugs that were brought were not allowed to be consumed without a doctor's prescription.